Intrinsic and extrinsic factors influencing the clinical course of B-cell chronic lymphocytic leukemia: prognostic markers with pathogenetic relevance - Dal-Bo, Michele (BioMed Central, 2009)
B-cell chronic lymphocytic leukemia (CLL), the most frequent leukemia in the Western world, is characterized by extremely variable clinical courses with survivals ranging from 1 to more than 15 years. The pathogenetic factors playing a key role in defining the biological features of CLL cells, hence eventually influencing the clinical aggressiveness of the disease, are here divided into "intrinsic factors", mainly genomic alterations of CLL cells, and "extrinsic factors", responsible for direct microenvironmental interactions of CLL cells; the latter group includes interactions of CLL cells occurring via the surface B cell receptor (BCR) and dependent to specific molecular features of the BCR itself and/or to the presence of the BCR-associated molecule ZAP-70, or via other non-BCR-dependent interactions, e.g. specific receptor/ligand interactions, such as CD38/CD31 or CD49d/VCAM-1. A putative final model, discussing the pathogenesis and the clinicobiological features of CLL in relationship of these factors, is also provided.